Monologue and Organization Studies. Issue 9 (September 2022) - Izak, Michal; Case, Peter; Ybema, Sierk
In this essay, we propose that recent work in management and organization studies is typically inclined to understand organization and organizing as dialogic in form. Dialogicity is characterized by dynamic interlocution on the part of active human sense-makers and, in our critical reading, evokes a romanticized social landscape that fails to reflect the more prosaic features of organizational life. To address what we see as certain limitations of the dialogic view, we introduce a complementary point of reference: that of monologic organization. This perspective provokes reflection on those situations in which meanings are predetermined at the outset and communication consists of the strictly controlled, routine reproduction of formal scripts. We draw on the works of Mikhail Bakhtin and Michel Serres to reclaim monologic as a pertinent view of organization and its processes. Finally, we provide micro-, meso- and macro-level examples to illustrate and discuss the heuristic potential of a monologic view.